Black soldier fly life history traits can be influenced by isonutrient-waste-based diets - Sara Bellezza Oddon; Ilaria Biasato; Andrea Resconi; Laura Gasco (Italian Journal of Animal Science, 2024)
To maximise the black soldier fly (BSF) bioconversion capacity, a waste that is not suitable for use as it is, can have a positive effect if combined with others in a formulation. In this perspective, a total of 3600 of 6-day-old larvae were inoculated on 6 iso-proteic, iso-lipidic and iso-energetic diets (named from D1 to D6; 100 larvae/replicate; 6 replicates/treatment) formulated with 21 by-products. To evaluate growth performance, 30 larvae per replicate were randomly sampled every 4 days until the 40% reached the prepupae phase, in which survival rate (SR), larva-prepupae time duration and bioconversion indexes were calculated. When a pupa was identified, it was moved in the emergence box (23 pupae/treatment) to evaluate the adult parameters: pupa-fly duration time, fly live weight, weight reduction, fly lifespan, puparium weight and emergence rate (ER). Considering SR (>92%) and ER (>94.6%), all diets were suitable for the BSF breeding. The D1 and D5 (composed by brewers spent grain, vegetable and fruit waste) groups overall performed the best larvae growth and development time, while D2 (composed by glaze waste and buffalo milk whey) displayed the worst (p < 0.05). The D5 maintained good weight in prepupae, pupae and adult stages and also D2 reached the same outcome. The bioconversion indexes followed the trend of the larvae performance. In conclusion, the results herein obtained allowed to discriminate the protein, fat and energy variables on the BSF life history traits and observe other factors of influence, such as the ash content, which will need to be evaluated with future research.